2022
DOI: 10.3390/vaccines10071052
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Zero-Dose Vaccination Status among Children Aged 12–59 Months in Sub-Saharan Africa: A Multilevel Analysis of Individual and Contextual Factors

Abstract: Despite ongoing efforts to improve childhood vaccination coverage, including in hard-to-reach and hard-to-vaccinate communities, many children in sub-Saharan Africa (SSA) remain unvaccinated. Considering recent goals set by the Immunization Agenda 2030 (IA2030), including reducing the number of zero-dose children by half, research that goes beyond coverage to identify populations and groups at greater risk of being unvaccinated is urgently needed. This is a pooled cross-sectional study of individual- and count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
(75 reference statements)
2
6
2
Order By: Relevance
“…The Mozambique study identified similar patterns of barriers to vaccination, including the role of gender barriers and power imbalances with health workers. Cross-national quantitative analyses of household survey data show that immunization inequalities are associated with household wealth and maternal education [ 6 ], and that the prevalence of zero-dose children is associated with gender inequality [ 8 ], birth order, birth weight, maternal education, maternal occupation, household wealth, and the number of antenatal care visits [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mozambique study identified similar patterns of barriers to vaccination, including the role of gender barriers and power imbalances with health workers. Cross-national quantitative analyses of household survey data show that immunization inequalities are associated with household wealth and maternal education [ 6 ], and that the prevalence of zero-dose children is associated with gender inequality [ 8 ], birth order, birth weight, maternal education, maternal occupation, household wealth, and the number of antenatal care visits [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research exists on the drivers of immunization inequality [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ], yet most of the existing research focuses either on individual attributes or health system drivers, without analysis of the social and structural processes that produce inequalities [ 11 ]. Recent attention to the role of gender in immunization (in)equity is overdue [ 8 , 12 ] but too often, gender is explored alone, without consideration of how it intersects and interacts with other social, institutional, and structural dimensions of inequality, including social determinants of health.…”
Section: Introductionmentioning
confidence: 99%
“…The nding was supported by a study in national studies, and Afghanistan [20,21,22]. This could explain by in wealth index, study shows that countries with high wealth index within each country; As a result, even when few people earn substantial salaries, countries with high natural resource revenues may appear to nd better services in vaccination and health care than others [23].…”
Section: Discussionmentioning
confidence: 84%
“…The ongoing COVID-19 pandemic has contributed to at least some of today’s gaps in childhood vaccination [ 3 ], with estimates of under-one children without any doses of the diphtheria–tetanus–pertussis vaccine (no-DTP) rising from 10% prevalence in 2019 to 14% in 2021 [ 3 ]. Communities with high levels of unvaccinated or “zero-dose children” often face myriad vulnerabilities [ 4 , 5 , 6 , 7 ], such as residing in highly remote areas or informal settlements in cities [ 7 , 8 , 9 ]; being affected by displacement and/or prolonged conflict or unrest [ 7 , 8 ]; longstanding poverty and/or societal neglect [ 4 ]; or some constellation of these factors. Subsequently, optimally identifying where and how to better reach zero-dose children will likely require a combination of context-specific strategies and broader investments to address persisting structural challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, a growing body of research has sought to assess characteristics of zero-dose children and their families or households, as well as potential drivers of high zero-dose prevalence at different geographic levels [ 4 , 5 , 6 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Past work has found that zero-dose children experience a higher odds of missing or lacking access to other types of primary care services [ 6 , 11 , 12 ], while their mothers were more likely to have no antenatal care visits and not deliver at a health facility [ 11 , 12 ]. Lower levels of household wealth, educational attainment, and measures of women’s empowerment also have been associated with higher levels of zero-dose children [ 4 , 10 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%